An extremely rare case of tubo-ovarian abscesses involving corynebacterium striatum as causative agent. Issue 1 (December 2016) - Yamamoto, Tetsuya; Kenzaka, Tsuneaki; Mizuki, Shimpei; Nakashima, Yuki; Kou, Houu; Maruo, Motoyoshi; Akita, Hozuka
Abstract Background We present an extremely rare case of tubo-ovarian abscesses involvingCorynebacterium striatum (C. striatum ) as causative agent in a 53-year-old woman. Case presentation The patient presented with stomach pain, chills, and nausea. Her medical history included poorly controlled psoriasis vulgaris and diabetes. Laboratory and imaging findings led to diagnosis of septic shock due to tubo-ovarian abscesses. She was treated with antibiotic therapy and surgery to remove the left adnexa. Various cultures detectedPrevotella spp. andC. striatum . We concluded thatC. striatum from skin contaminated by psoriasis vulgaris had caused the tubo-ovarian abscesses by way of ascending infection. Conclusions This may be the first known case of tubo-ovarian abscesses due toC. striatum . In patients whose skin has been weakened by psoriasis vulgaris or other infections, Corynebacterium should be considered as causative microorganisms, and antibiotic therapy including vancomycin should be administered.